Penerapan Metode Simple Additive Weighting Dalam Pemilihan Guru Terbaik Pada SDN Duri Kepa 07 - Muhammad Kurnia Affandi; Humisar Hasugian; Wulandari Wulandari; Nofiyani Nofiyani (Universitas Budi Luhur, 2025)
Fair and objective teacher performance evaluation is essential for improving the quality of education. However, the process of selecting outstanding teachers at the elementary school level is often conducted subjectively without a structured approach.. This study aims to develop a web-based decision support system using the Simple Additive Weighting (SAW) method to enhance teacher performance evaluation based on measurable criteria. The system utilizes seven primary criteria, Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative. Each criterion is assigned a specific weight used to calculate the final preference value for each teacher as an alternative. System validation was carried out through Black Box Testing, White Box Testing, and User Acceptance Testing (UAT) involving end users. The test results indicate that all system features function properly and are capable of accurately displaying the teacher ranking order. One teacher achieved the highest preference score, demonstrating the effectiveness of the SAW method in supporting objective and efficient decision-making. The system has the potential to be widely implemented to improve clarity and accountability in teacher performance evaluation.